Role of the Dihydrodipicolinate Synthase DapA1 on Iron Homeostasis During Cyanide Assimilation by the Alkaliphilic Bacterium Pseudomonas pseudoalcaligenes CECT5344 - Olaya-Abril, Alfonso; Pérez, María Dolores; Cabello, Purificación; Martignetti, Diego; Sáez, Lara Paloma; Luque-Almagro, Víctor Manuel; Moreno-Vivián, Conrado; Roldán, María Dolores (Frontiers in Microbiology, 2020)
Cyanide is a toxic compound widely used in mining and jewelry industries, as well as in the synthesis of many different chemicals. Cyanide toxicity derives from its high affinity for metals, which causes inhibition of relevant metalloenzymes. However, some cyanide-degrading microorganisms like the alkaliphilic bacterium Pseudomonas pseudoalcaligenes CECT5344 may detoxify hazardous industrial wastewaters that contain elevated cyanide and metal concentrations. Considering that iron availability is strongly reduced in the presence of cyanide, mechanisms for iron homeostasis should be required for cyanide biodegradation. Previous omic studies revealed that in the presence of a cyanide-containing jewelry residue the strain CECT5344 overproduced the dihydrodipicolinate synthase DapA1, a protein involved in lysine metabolism that also participates in the synthesis of dipicolinates, which are excellent metal chelators. In this work, a dapA1ˉ mutant of P. pseudoalcaligenes CECT5344 has been generated and characterized. This mutant showed reduced growth and cyanide consumption in media with the cyanide-containing wastewater. Intracellular levels of metals like iron, copper and zinc were increased in the dapA1ˉ mutant, especially in cells grown with the jewelry residue. In addition, a differential quantitative proteomic analysis by LC-MS/MS was carried out between the wild-type and the dapA1ˉ mutant strains in media with jewelry residue. The mutation in the dapA1 gene altered the expression of several proteins related to urea cycle and metabolism of arginine and other amino acids. Additionally, the dapA1ˉ mutant showed increased levels of the global nitrogen regulator PII and the glutamine synthetase. This proteomic study has also highlighted that the DapA1 protein is relevant for cyanide resistance, oxidative stress and iron homeostasis response, which is mediated by the ferric uptake regulator Fur. DapA1 is required to produce dipicolinates that could act as iron chelators, conferring protection against oxidative stress and allowing the regeneration of Fe-S centers to reactivate cyanide-damaged metalloproteins.